2018
DOI: 10.1021/acsmedchemlett.8b00352
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Dual Inhibition of Carbonic Anhydrase and Cyclooxygenase by Dihydrothiazole Benzensulfonamides

Abstract: A novel series of of 4-[(3-phenyl-4-aryl-2,3-dihydro-1,3-thiazol-2-ylidene)amino]benzene-1-sulfonamides (EMAC10111a−g) was synthesized and assayed toward both human carbonic anhydrase isozymes I, II, IX, and XII and cyclooxygenase isoforms. The majority of these derivatives preferentially inhibit hCA isoforms II and XII and hCOX-2 isozyme, indicating that 2,3,4-trisubstituted 2,3-dihydrothiazoles are a promising scaffold for the inhibition of hCA isozymes and of hCOX-2 enzyme. The nature of the substituent at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…In case of hCA XII, the presence of dihalogens was beneficial, following the order 2,4-di-F > 2.4-di-Cl. Final- Based on their previous observations [278][279][280][281], Distinto et al [282] designed a library of 4-[(3-methyl-4-aryl-2,3-dihydro-1,3-thiazol-2-ylidene)amino] benzene-1-sulphonamides and synthesized in order to evaluate the effect of substituents in positions 3 and 4 of the dihydrothiazole ring on the inhibitory potency and selectivity toward human carbonic anhydrase isoforms I, II, IX, and XII. The study revealed that in accordance with their previous observations for compounds with similar structure, none of the synthesized compounds was active against hCA I isoform.…”
Section: Thiazole Derivatives As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%
“…In case of hCA XII, the presence of dihalogens was beneficial, following the order 2,4-di-F > 2.4-di-Cl. Final- Based on their previous observations [278][279][280][281], Distinto et al [282] designed a library of 4-[(3-methyl-4-aryl-2,3-dihydro-1,3-thiazol-2-ylidene)amino] benzene-1-sulphonamides and synthesized in order to evaluate the effect of substituents in positions 3 and 4 of the dihydrothiazole ring on the inhibitory potency and selectivity toward human carbonic anhydrase isoforms I, II, IX, and XII. The study revealed that in accordance with their previous observations for compounds with similar structure, none of the synthesized compounds was active against hCA I isoform.…”
Section: Thiazole Derivatives As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%
“…2-Iminothiazolines are biologically active compounds represented by selective cannabinoid receptor type 2 (CB2) agonists, [1][2][3][4] carbonic anhydrase (CA), cyclooxygenase (COX) and lipoxygenase (LOX) inhibitors, [5][6][7][8][9] anticancer [10,11] and antithrombotic agents, [12] HIV1 reverse transcriptase inhibitors [13] and fungicides (Figure 1). [14] Similarly, related 2-aminothiazoles showed anticancer, [15][16][17][18] antibacterial, [19] anticonvulsant, antidiabetic, antihypertensive, anti-inflammatory, antiviral, antimicrobial and neuroprotective activities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, synthesis of new sulphonamide derivatives is an active research topic for organic and pharmaceutical chemists 8, 9 . Both sulphonamides [10][11][12] and amino acids [13][14][15] have been reported to have various biological activities, but there are few reports of their successful combination in one molecule as a hybrid drug candidate [16][17][18] . Due to their antimicrobial and CA inhibitory properties, both primary and secondary sulphonamide derivatives are under investigation to determine compounds possessing the highest activity with possibly few side-effects 19,20 .…”
Section: Introductionmentioning
confidence: 99%